Manajemen Peserta Didik Perspektif Kitab Adᾱb Al ‘Ᾱlim Wa Al-Muta’allim Karya KH. M. Hasyim Asy’ari - Ma’sum, Toha; Ristianah, Niken (STAI Ihyaul Ulum Gresik, 2021)
Studying learners in the melenial paradigm is a very important and interesting study. Therefore, we can find out the extent to which students are engaged in facing the educational horizon in Indonesia. Related to the urgency of learners facing the millennial era researchers want to examine more in more closely how the management of learners in general and more especially according to the view of the book Adb al 'lim wa al Muta'allim related to the concept of student management. the results of research and discussions that have been previously described, concluded that the concept of student management is a plan that will be carried out in the management of learners in which there is an understanding of student management, the objectives and functions of student management, the principles of student management, and also the management activities of learners, the concept of learners perspective of the book of Adb al 'lim wa al Muta'allim is a plan that must be owned by the learner that has full concentration, has high morality and motivation, the concept of management of learners perspective of the book Adb al 'lim wa al Muta'allim that the learner must plan what will be done when starting to find knowledge that is there is intention, grouping learners when learning , student orientation, coaching and development of learners, evaluation and mutation. Referencing the results of this study, there are several suggestions that in the concept of student management, schools or institutions should pay close attention to what is needed by the learner so that what is planned by the school or institution can be achieved properly. In addition, based on the analysis of the Book of Adb Al 'lim Wa Al Muta'allim, related to the concept of student management, students should be able to do anything that is an obligation for learners.